Fuzzy Logic Untuk Menentukan Kepuasan Siswa Terhadap Sarana dan Prasarana Sekolah Dengan Menggunakan Metode Sugeno - Yulia S.Kom.,M.Kom (JURNAL ILMIAH INFORMATIKA, 2018)
Education is a communication activity that essentially is the delivery and exchange of messages to the learners. Educational tools are considered to help the success of the educational process. Educational tools are tools and equipments that are directly used and support the educational process, especially the teaching and learning process, such as buildings, classrooms, desks, and tools and teaching media. But sometimes students' satisfaction with school facilities can not be a support for the alignment of the learning process itself, which ultimately affects the passing standards, student conditions, achievement, academic, non-academic achievement, personality, management, leadership, curriculum, teachers, principals, support staff, organization and administration, infrastructure, financing, school regulation, public relations and school culture. Fuzzy logic is a way to map an input space into an output space. With fuzzy logic something that can have values ​​between range 0 and 1. "Fuzzy" means blurred or vague. Fuzzy logic is believed to be very flexible and also has data tolerance. With the application of fuzzy logic in decision support by using Sugeno method is expected to produce a model so that decisions are taken exactly on target and in accordance with the expected.